2014
DOI: 10.1194/jlr.m043281
|View full text |Cite
|
Sign up to set email alerts
|

High density lipoproteins improve insulin sensitivity in high-fat diet-fed mice by suppressing hepatic inflammation

Abstract: Obesity-induced liver inflammation can drive insulin resistance. HDL has anti-inflammatory properties, so we hypothesized that low levels of HDL would perpetuate inflammatory responses in the liver and that HDL treatment would suppress liver inflammation and insulin resistance. The aim of this study was to investigate the effects of lipid-free apoAI on hepatic inflammation and insulin resistance in mice. We also investigated apoAI as a component of reconstituted HDLs (rHDLs) in hepatocytes to confirm results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
(49 reference statements)
3
32
0
Order By: Relevance
“…The infusion of exogenous reconstituted HDL-C potentiated both insulin secretion and skeletal muscle glucose uptake in a small trial with type 2 diabetic patients [32]. ApoA-I treatment was found to increase glucose-stimulated insulin secretion in mice that were fed a high-fat diet [33, 34] and ameliorated β-cell dysfunction by inhibiting β-cell apoptosis [9, 35]. The favourable effects of apoA-I on improving insulin sensitivity have been further investigated in human skeletal muscle cells and adipocytes, in which both HDL-C and apoA-I promoted glucose uptake independently of insulin stimulation [32, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…The infusion of exogenous reconstituted HDL-C potentiated both insulin secretion and skeletal muscle glucose uptake in a small trial with type 2 diabetic patients [32]. ApoA-I treatment was found to increase glucose-stimulated insulin secretion in mice that were fed a high-fat diet [33, 34] and ameliorated β-cell dysfunction by inhibiting β-cell apoptosis [9, 35]. The favourable effects of apoA-I on improving insulin sensitivity have been further investigated in human skeletal muscle cells and adipocytes, in which both HDL-C and apoA-I promoted glucose uptake independently of insulin stimulation [32, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment with HDL or apoA-I increases insulin secretion and production in isolated pancreatic islets and insulinoma beta cell lines [7,8]. Recent studies have demonstrated that both single and repeated doses of apoA-I can also improve insulin resistance in fat-fed C57Bl6 mice [9,10], as can overexpression of apoA-I [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, this association has not been found to be consistent in previous studies [22][23][24][25] although previous research suggested that ApoA1 affects glucose metabolism via multiple mechanisms, including enhanced insulin secretion [26], increased insulin-independent glucose uptake in muscle and adipose tissues [27,28], improved insulin sensitivity [29], and reversed adipocyte dysfunction [30] and restored adiponectin expression and insulin sensitivity [31] with ApoA1 mimetic peptide. Furthermore, genetic studies suggested that genetic variation in ABCA1 has been associated with the increased risk of T2DM [32], and one study suggested that loss-of-function mutations in ABCA1 were associated with impaired b-cell function, but not with the development of T2DM [33].…”
Section: Discussionmentioning
confidence: 44%